ALGORITM CORRECTION SCORE TEST BASED ON ANALYSIS COMPLEXITY OF TASKS (Journal of Information Technologies in Education (ITE), 2014)
Purpose of work is develop an algorithm corrections test scores based on the analysis of complexity test questions. In this paper the tests with a closed form of the question are described.Corrections of test scores required for the differentiation of test participants who have scored equal test scores. The paper presents the main steps of the algorithm corrections of test results and present calculations that show the effectiveness of the algorithm. For the calculations used for data analysis packages such as SPSS and MS Excel.
Keywords: tests; test questions complexity; corrections test scores; a linear transformation